2019
DOI: 10.1111/1468-5973.12275
|View full text |Cite
|
Sign up to set email alerts
|

Two sides of the same coin: Business resilience and community resilience

Abstract: The resilience of small businesses and how that relates to community resilience, especially in rural communities has remained an under‐researched aspect of community resilience. This exploratory study aims to understand the relationship between business resilience and community resilience in rural communities. Firstly, the research seeks to understand the role that small businesses play in contributing to community resilience activities. The paper then sheds light on enabling and challenging factors that shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…For example, the results will provide scholars with a better understanding of the types of public, private and nonprofit organizations that engage in disaster preparedness as well as the kinds of preparedness measures these organizations adopt. This study also continues conversations occurring within the crisis management field that underscore how engaging organizations from the public, private and nonprofit sector can help improve communities' resilience to future disasters (Adekola & Clelland, ; Darkow, ; Torres, Marshall, & Sydnor, ).…”
Section: Introductionmentioning
confidence: 72%
“…For example, the results will provide scholars with a better understanding of the types of public, private and nonprofit organizations that engage in disaster preparedness as well as the kinds of preparedness measures these organizations adopt. This study also continues conversations occurring within the crisis management field that underscore how engaging organizations from the public, private and nonprofit sector can help improve communities' resilience to future disasters (Adekola & Clelland, ; Darkow, ; Torres, Marshall, & Sydnor, ).…”
Section: Introductionmentioning
confidence: 72%
“…They stressed that small business disaster recovery should encompass the individual, family, and community context, as these factors are important in recovery from a natural disaster. Adekola and Clelland ( 2019 ) also found that rural, small businesses had a major influence on community resilience after natural disasters. Small business owners were often volunteers who contributed individually to community recovery.…”
Section: Review Of Literaturementioning
confidence: 97%
“…In the context of business and community, ECSR practices can improve community development (Fordham, Robinson, & Van Leeuwen, 2018) and increase community capacity as an effort to express the capacity and collective community (Rama, Milano, Salas, & Liu, 2009). A recent study by Adekola and Clelland (2020) has concluded that business resilience can improve individual resilience. This study analyses the effects of ECSR on the EWB of the community by mediating community resilience.…”
Section: Introductionmentioning
confidence: 99%